Contraction of surfactant-laden pores - Liu, Jiakai (2018)
The contraction of surfactant-laden pores at the microscale has implications fornatural and technological processes ranging from the collapse of channels in lipid mem-branes to the stability of foams in the food processing industry. Despite its prevalence,our understanding of the mechanisms of pore contraction in the presence of surfactantsremains unclear. These mechanisms have been challenging to study experimentallygiven the small length scale near the singularity and simulations capable of accuratelycharacterizing the pore dynamics may help enhance our understanding of the process.Here, we use high-fdelity numerical simulations to gain insight into the uid dynamicsand interfacial phenomena underlying the contraction of viscous pores in the presenceof an insoluble surfactant. The simulations show that surfactants accumulate on theadvancing front of a collapsing pore due to the uneven deformation of the pore inter-face. Because of this accumulation, even a small amount of surfactant plays a major role in the way in which a collapsing pore approaches the singularity.